2020
DOI: 10.1093/jfr/fjaa010
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Finance

Abstract: DeFi (‘decentralized finance’) has joined FinTech (‘financial technology’), RegTech (‘regulatory technology’), cryptocurrencies, and digital assets as one of the most discussed emerging technological evolutions in global finance. Yet little is really understood about its meaning, legal implications, and policy consequences. In this article we introduce DeFi, put DeFi in the context of the traditional financial economy, connect DeFi to open banking, and end with some policy considerations. We suggest that decen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
122
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(127 citation statements)
references
References 0 publications
0
122
0
5
Order By: Relevance
“…The benefits of DeFi and its limitations are studied by Chen et al [3]. A similar work is presented by Zetzsche et al [1], where they demonstrated several perspectives of how DeFi differed from traditional financial systems. They have gathered resources to architect the security concerns that DeFi poses to institutions and people and summarizes how DeFi can be regulated.…”
Section: Related Workmentioning
confidence: 79%
See 3 more Smart Citations
“…The benefits of DeFi and its limitations are studied by Chen et al [3]. A similar work is presented by Zetzsche et al [1], where they demonstrated several perspectives of how DeFi differed from traditional financial systems. They have gathered resources to architect the security concerns that DeFi poses to institutions and people and summarizes how DeFi can be regulated.…”
Section: Related Workmentioning
confidence: 79%
“…Decentralized Finance (DeFi) is inspired by FinTech 1 and the practical applicability of blockchain technology. Blockchain technology offers a decentralized, transparent platform for finance with no intermediaries for exchanges [1]. Lee et al, in their journal [2] defines FinTech and disruption of FinTech in modern times: the digital evolution of financial services provided to customers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Схожей позиции придерживаются ученые Дирк А. Зетше, Дуглас В. Арнер и Росс П. Бакли [3]. В работе, посвященной децентрализованным финансам, они предположили, что данное направление в будущем может быть ассимилировано традиционным финансовым сектором.…”
unclassified